Dual burden of chronic physical conditions and mental disorders: Findings from the Saudi National Mental Health Survey - Yasmin Altwaijri; Yasmin Altwaijri; Yasmin Altwaijri; Abdulhameed Al-Habeeb; Abdullah Al-Subaie; Abdullah Al-Subaie; Ronny Bruffaerts; Lisa Bilal; Lisa Bilal; Lisa Bilal; Sanaa Hyder; Sanaa Hyder; et al. (Frontiers Media S.A., 2023)
IntroductionComorbidities of mental disorders and chronic physical conditions are a common medical burden reported among Western countries. National estimates of such comorbidities among the general population of Arab countries like Saudi Arabia are unknown. This study examined the prevalence of lifetime chronic physical conditions among the Saudi general population with DSM-IV 12-month mental disorders, and the associations with disability in the Kingdom of Saudi Arabia (KSA).MethodsThe Saudi National Mental Health Survey, a cross-sectional household study - part of the World Mental Health (WMH) Survey Consortium - was conducted between 2013-2016 in the KSA, with 4,001 Saudi citizens aged 15-65 (response rate 61%). The World Health Organization Composite International Diagnostic Interview 3.0 was used to assess prevalence of lifetime chronic physical conditions and 12-month mental disorders; disability was measured in terms of days out of role.ResultsThe prevalence of any comorbid 12-month mental disorder among those with chronic physical conditions was 24%. Major depressive disorder, social phobia, and adult separation anxiety disorder were the most common comorbid mental disorders across all chronic physical conditions. Gender, education, income, urbanicity, region, and employment were associated with the presence of any chronic physical condition. Respondents with mental / physical comorbidities had 2.97 days out of role (on average) in the last 30 days.ConclusionComorbidities of mental disorders and chronic physical conditions are common among Saudis. National efforts are needed to increase awareness of such comorbidities among the general population, and develop prevention and treatment services tailored to the needs of individuals at-risk for comorbidities.